(untitled) (Research, Society and Development, 2021)
The objective was to understand the perception of a team of collaborators about the applicability of the INDICAH System as a quality management tool in a hematology center in a municipality in northeastern Brazil. This is a qualitative and descriptive study carried out with the participation of 23 workers assigned to the institution where the study was carried out, which took place from February to April 2020. For data collection, the focus group technique was used. Two categories were extracted from the narratives: Strategies for improving the quality indicator system and Strategies for easily accessing the indicators. The interpretation of the categories occurred through thematic analysis of Bardin. The speeches recorded in the focus groups were transcribed into a Word document, then they were inserted in the Atlas-ti software, version 8.4.24.0, which favored the coding of the data and the organization into categories and subcategories. The study made it possible to understand the perception of the team of workers in relation to the applicability of the INDICAH System as a quality management tool in HEMOCE. These findings contribute to the planning of strategies to improve quality management through the use of indicators, such as better communication, sectorial relations, greater dissemination of indicators and ways to win the donor shaped according to local needs.